Dynamic state power system fault monitoring and protection with phasor measurements and fuzzy based expert system - Ravi Ponnala; Muktevi Chakravarthy; Suraparaju Venkata Naga Lakshmi Lalitha (Bulletin of Electrical Engineering and Informatics, 2022)
The main aim of this paper is building of a small micro grid test bed system with a few sources, and few loads with various types of lumped resistive (R), capacitive (C) and inductive (L) elements. Before the advent of electric smart grid every load is facilitated with its own electromagnetic. Slowly with an advancement of protection system numerical relays came into existence. Because in the numerical relays the communication between the relays and communication with central computer is possible, with this a coordinative protection system was evolved. For the monitoring and protection of system in dynamic state many of the numerical relays were now replaced by intelligent electronic devices. The system is to be centrally controlled with an improvement in data communications and the artificial intelligence into power system made it is possible to control the power system centrally. In this paper, it is presented that the fault is monitoring and protection against different types of faults, such as frequency variations, voltage variations and different fault conditions using fuzzy based expert system (FBES). The proposed protection scheme is adaptive for frequency variations, voltage variations and fault levels. The FBES scheme is implemented in the LabVIEW software with MAMDANI structure.